Description of a new species of the genus Neolucanus Thomson, 1862 (Coleoptera: Lucanidae) from central Vietnam - Nguyen, Thai Quang (Zootaxa, 2013)
Neolucanus baongocae new species is described from Lam Dong Province (Central Vietnam) and compared to closely related Neolucanus taxa.